Composite aluminum-plastic film for secondary battery and secondary battery

By introducing a thermally conductive bonding layer and a water-blocking and breathable layer into the aluminum-plastic film of lithium-ion batteries, and using the thermal decomposition reaction of heat-absorbing particles, the problem of thermal runaway in lithium-ion batteries is solved, achieving better heat box performance and Safety performance.

CN119208807APending Publication Date: 2024-12-27ZHEJIANG LIWINON ENERGY TECHNOLOGY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411191448.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-08-27
Publication Date
2024-12-27

AI Technical Summary

Technical Problem

Lithium-ion batteries are prone to thermal runaway when the temperature is too high, and existing aluminum-plastic films are difficult to effectively absorb heat and prevent or prolong the thermal runaway time, affecting battery safety.

Method used

Design a composite aluminum-plastic film, including a heat sealing layer, an aluminum foil layer, a thermal bonding layer and a water-blocking and breathable layer, the thermal bonding layer contains heat-absorbing and breathable layer, and the water-blocking and breathable layer has multiple micropores, and the heat-absorbing particles are in The gas is thermally decomposed at a predetermined temperature to enhance the heat dissipation effect.

Benefits of technology

This composite aluminum-plastic film can quickly absorb heat when the battery temperature is too high, extend the thermal runaway time, improve the battery's heat box performance and safety performance, and ensure that the battery does not catch fire or explode at high temperatures.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119208807A_ABST
    Figure CN119208807A_ABST
Patent Text Reader

Abstract

The invention belongs to the technical field of secondary batteries, and particularly relates to a composite aluminum-plastic film for a secondary battery and the secondary battery. The composite aluminum-plastic film sequentially comprises an aluminum foil layer, a heat-conducting bonding layer and a water-blocking breathable layer from inside to outside, a plurality of pores are distributed in the surface of the waterproof breathable layer, the pore diameter of the pores is R1, the particle size of water drops is R2, and the particle size of water vapor molecules is R3; wherein R1, R2 and R3 meet the relation that R1 is larger than R3 and smaller than R2; and the heat-conducting bonding layer comprises a heat-conducting adhesive and heat-absorbing particles distributed in the heat-conducting adhesive. Compared with the prior art, the waterproof breathable layer is adopted to replace a nylon layer of an existing aluminum plastic film, internal steam and other gases can be discharged out of the battery while external steam is isolated, and when the temperature of the battery is too high, heat can be rapidly absorbed to avoid thermal runaway of the battery or prolong the thermal runaway time, and the heat dissipation performance is improved; and the hot box performance of the battery is improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of secondary batteries, and in particular to a composite aluminum-plastic film for secondary batteries and a secondary battery. Background Art

[0002] As the energy density of lithium-ion batteries increases, the issue of battery safety is becoming increasingly prominent. In response to the problem of battery thermal runaway, the Ministry of Industry and Information Technology began to implement three mandatory national standards in 2021, which clearly require that after a battery cell experiences thermal runaway, it must not catch fire or explode within 5 minutes, leaving safe escape time for the occupants. It can be seen that the research on thermal runaway of lithium-ion batteries is urgent and determines the future popularization and development of the new energy vehicle industry.

[0003] However, when the battery temperature exceeds the threshold, it will trigger an exothermic chain reaction between the internal component materials (positive electrode, negative electrode and electrolyte, etc.), including the decomposition and regeneration reaction of the solid electrolyte interface film (SEI film), the reaction between the electrolyte and the electrode material, the reaction between the binder and the negative electrode, the redox reaction between the positive electrode and the negative electrode, etc. The aluminum-plastic composite film is a composite material composed of an outer nylon layer, an intermediate aluminum foil layer, and an inner heat-sealing layer. The layers are pressed and bonded by adhesives. The aluminum-plastic film is a key material for the packaging of soft-package lithium batteries. After the single-chip battery is assembled, it is sealed with the aluminum-plastic film to form a battery, and the aluminum-plastic film plays a role in protecting the contents.

[0004] Therefore, it is necessary to develop a composite aluminum-plastic film with excellent hot box performance. Summary of the invention

[0005] The purpose of the present invention is to provide a composite aluminum-plastic film to address the deficiencies of the prior art, which can quickly absorb heat when the battery temperature is too high to avoid thermal runaway of the battery or prolong the thermal runaway time, so as to achieve excellent hot box performance.

[0006] In order to achieve the above object, the present invention adopts the following technical solutions:

[0007] A composite aluminum-plastic film for a secondary battery, comprising, from the inside to the outside, a heat-sealing layer, an aluminum foil layer, a heat-conducting adhesive layer, and a water-blocking and air-permeable layer; a plurality of pores are distributed on the surface of the water-blocking and air-permeable layer, the pore size of the pores is R1, the particle size of the water droplets is R2, and the particle size of the water vapor molecules is R3; wherein R1, R2, and R3 satisfy the relationship: R3<R1<R2;

[0008] The thermally conductive adhesive layer includes a thermally conductive adhesive and heat absorbing particles distributed in the thermally conductive adhesive.

[0009] Preferably, the water-blocking and breathable layer is expanded polytetrafluoroethylene.

[0010] Preferably, the heat absorbing particles can be thermally decomposed to generate gas at a predetermined temperature, and the predetermined temperature for thermal decomposition is 100°C-150°C.

[0011] Preferably, the thermally conductive adhesive layer has a thickness of 5-10 μm.

[0012] Preferably, the particle size of the heat absorbing particles is 0.5-3 μm.

[0013] Preferably, the doping amount of the heat absorbing particles is 30-50%.

[0014] Preferably, the composite aluminum-plastic film further comprises a heat-sealing layer, and the heat-sealing layer is coated on the inner surface of the aluminum foil layer.

[0015] Preferably, the thermally conductive adhesive is silicone grease.

[0016] Preferably, the heat absorbing particles are urea.

[0017] In addition, the present invention also provides a secondary battery, comprising the above-mentioned composite aluminum-plastic film.

[0018] Compared with the prior art, the beneficial effect of the present invention is that the present invention uses a water-blocking and breathable layer to replace the nylon layer of the existing aluminum-plastic film, which can ensure the isolation of external water vapor while allowing internal water vapor and other gases to be discharged from the battery. When the battery temperature is too high, it can quickly absorb heat to avoid thermal runaway of the battery or prolong the time of thermal runaway, improve the heat dissipation performance, and thus improve the hot box performance of the battery. In addition, the present invention sets a thermally conductive adhesive layer between the water-blocking and breathable layer and the aluminum foil layer, which acts as an adhesive to ensure a stable connection between the two layers of materials. The thermal conductivity of the thermally conductive adhesive layer can promote the efficient transfer of heat absorbed by the aluminum foil layer to the water-blocking and breathable layer; and heat-absorbing particles are added to the thermally conductive adhesive layer. When the battery temperature reaches a predetermined temperature, the heat-absorbing particles will undergo a thermal decomposition reaction to produce gas. The gas produced by the thermal decomposition is discharged from the battery through the water-blocking and breathable layer, which can take away more heat. Therefore, the design of the thermally conductive adhesive layer cleverly utilizes the heat absorption and gas production characteristics of the material, forming a synergistic effect with the water-blocking and breathable layer, further improving the hot box performance and safety performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is one of the structural schematic diagrams of the composite aluminum-plastic film for secondary batteries of the present invention.

[0020] Figure 2 This is the second structural schematic diagram of the composite aluminum-plastic film for secondary batteries of the present invention.

[0021] Among them, 1-aluminum foil layer; 2-thermal conductive adhesive layer; 3-heat absorbing particles; 4-water-blocking and breathable layer; 5-heat sealing layer. DETAILED DESCRIPTION

[0022] To make the technical solutions and advantages of the present invention clearer, the following will, in conjunction with specific embodiments, clearly and completely describe the technical solutions of the present invention. Obviously, the described embodiments are some embodiments of the present invention, rather than all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those of ordinary skill in the art without creative efforts fall within the scope of protection of the present invention.

[0023] As Figure 1 shown, according to the first aspect of the present application, the present application provides a composite aluminum-plastic film for secondary batteries, which sequentially includes an aluminum foil layer 1, a thermally conductive adhesive layer 2, and a water-blocking and breathable layer 4 from the inside to the outside; a plurality of pores are distributed on the surface of the water-blocking and breathable layer 4, the pore diameter of the pores is R1, the particle diameter of the water droplets is R2, and the particle diameter of the water vapor molecules is R3; wherein, R1, R2, and R3 satisfy the relationship: R3 < R1 < R2; the thermally conductive adhesive layer 2 includes a thermally conductive adhesive and heat-absorbing particles 3 distributed in the thermally conductive adhesive.

[0024] Among them, the present application uses a water-blocking and breathable layer to replace the nylon layer. Although the nylon layer has good isolation properties, it also isolates the internal gas components. While isolating external water vapor, it can allow internal water vapor and other gases to escape from the battery. When the battery temperature is too high, it can quickly absorb heat to avoid battery thermal runaway or extend the time of thermal runaway. The thermally conductive adhesive layer, as the adhesive between the aluminum foil layer and the water-blocking and breathable layer, ensures the adhesion between the two layers, and the heat-absorbing particles in the thermally conductive adhesive layer can thermally decompose and generate gas at a predetermined temperature and escape through the water-blocking and breathable layer.

[0025] In some embodiments, R1, R2, and R3 satisfy the relationship: 700R3 < R1 < 20000R2.

[0026] In some embodiments, the water-blocking and breathable layer 4 is expanded polytetrafluoroethylene. There are 1.4 billion micropores per square centimeter of expanded polytetrafluoroethylene. These micropores are 20,000 times smaller than water droplets but 700 times larger than water vapor molecules, which can isolate the outside while allowing internal water vapor and other gases to escape from the battery.

[0027] In some embodiments, the heat-absorbing particles 3 can thermally decompose and generate gas at a predetermined temperature, and the predetermined temperature of thermal decomposition is 100°C - 150°C. For example, it can be 100°C, 110°C, 120°C, 130°C, 140°C, 150°C.

[0028] In some embodiments, the thickness of the thermally conductive adhesive layer 2 is 5 - 10 μm. For example, it can be 5 μm, 6 μm, 7 μm, 8 μm, 9 μm, 10 μm. If the thickness is too thin, the heat dissipation improvement will be insufficient. If the thickness is too thick, the heat dissipation transfer to the aluminum layer will be slower, reducing the overall heat dissipation efficiency of the battery.

[0029] In some embodiments, the particle size of the heat absorbing particles 3 is 0.5-3 μm, for example, 0.5 μm, 1 μm, 1.5 μm, 2 μm, 2.5 μm, 3 μm. The smaller the particle size and the larger the surface area, the better the heat absorption effect. However, if the particle size is too small and the surface energy is too large, agglomeration is likely to occur.

[0030] In some embodiments, the doping amount of the heat absorbing particles 3 is 30-50%, for example, 30%, 35%, 40%, 45%, 50%. If the doping amount of the heat absorbing particles is too little, the heat absorption effect is insufficient, and if the doping amount of the heat absorbing particles is too much, the bonding force of the thermal conductive adhesive will decrease, and the aluminum foil layer and the water-blocking and breathable layer will not be bonded.

[0031] In some embodiments, Figure 2 As shown, the composite aluminum-plastic film further comprises a heat-sealing layer 5, which is coated on the inner surface of the aluminum foil layer 1. The heat-sealing layer 5 can be made of a material having a thermal bonding property such as PP and CPP.

[0032] In some embodiments, the thermally conductive adhesive is silicone grease. It should be noted that the thermally conductive adhesive may also be other materials with good thermal conductivity and bonding effects.

[0033] In some embodiments, the heat absorbing particles 3 are urea. It should be noted that the heat absorbing particles 3 may also be other substances that can be thermally decomposed to generate gas at a predetermined temperature.

[0034] According to a second aspect of the present application, the present application provides a secondary battery, comprising a battery cell and an aluminum-plastic film encapsulating the battery cell, wherein the aluminum-plastic film is the composite aluminum-plastic film for the secondary battery.

[0035] The positive electrode active material may include but is not limited to chemical formula such as Li a Ni x Co y M z O 2-b N b (wherein 0.95≤a≤1.2, x>0, y≥0, z≥0, and x+y+z=1, 0≤b≤1, M is selected from a combination of one or more of Mn and Al, and N is selected from a combination of one or more of F, P, and S) The positive electrode active material may also be, but is not limited to, LiCoO2, LiNiO2, LiVO2, LiCrO2, LiMn2O4, LiCoMnO4, Li2NiMn3O8, LiNi 0.5 Mn 1.5O4, LiCoPO4, LiMnPO4, LiFePO4, LiNiPO4, LiCoFSO4, CuS2, FeS2, MoS2, NiS, TiS2, etc. The positive active material may also be subjected to a modification treatment, and the method for modifying the positive active material should be known to those skilled in the art. For example, the positive active material may be modified by coating, doping, etc. The material used for the modification treatment may include but is not limited to a combination of one or more of Al, B, P, Zr, Si, Ti, Ge, Sn, Mg, Ce, W, etc. The positive current collector is usually a structure or part for collecting current, and the positive current collector may be various materials suitable for use as a positive current collector for lithium-ion batteries in the art. For example, the positive current collector may include but is not limited to metal foil, etc., and more specifically may include but is not limited to aluminum foil, etc.

[0036] The negative electrode plate includes a negative electrode current collector and a negative electrode active material layer coated on at least one surface of the negative electrode current collector. The negative electrode active material layer can be one or more of graphite, soft carbon, hard carbon, carbon fiber, mesophase carbon microspheres, silicon-based materials, tin-based materials, lithium titanate or other metals that can form alloys with lithium.

[0037] Among them, graphite can be selected from one or more of artificial graphite, natural graphite and modified graphite; silicon-based materials can be selected from one or more of elemental silicon, silicon oxide compounds, silicon carbon composites, and silicon alloys; tin-based materials can be selected from one or more of elemental tin, tin oxide compounds, and tin alloys. The negative electrode current collector is usually a structure or part that collects current. The negative electrode current collector can be any material suitable for use as a negative electrode current collector for lithium-ion batteries in the art. For example, the negative electrode current collector can include but is not limited to metal foil, and more specifically can include but is not limited to copper foil.

[0038] The binder can be a combination of one or more of polyvinylidene fluoride (PVDF), sodium alginate (SA), polyvinyl alcohol (PVA), polymethyl methacrylate (PMMA), hydrogenated nitrile rubber (HNBR), polytetrafluoroethylene (PTFE), polyacrylic acid (PAA), carboxymethyl cellulose (CMC), and styrene-butadiene rubber latex (SBR).

[0039] The conductive agent may be one or more combinations of acetylene black (AB), superconducting carbon black, graphite emulsion, carbon nanotube (CNT), graphene, Ketjen black (KB), vapor grown carbon fiber (VGCF), etc.

[0040] The secondary battery also includes an electrolyte, which includes an organic solvent, an electrolyte lithium salt and an additive. Among them, the electrolyte lithium salt can be LiPF6 and / or LiBOB used in high-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, and LiPF6 used in low-temperature electrolytes; it can also be at least one of LiBF4, LiBOB, LiPF6, and LiTFSI used in anti-overcharge electrolytes; it can also be at least one of LiClO4, LiAsF6, LiCF3SO3, and LiN(CF3SO2)2. The organic solvent can be a cyclic carbonate, including PC and EC; it can also be a chain carbonate, including DFC, DMC, or EMC; it can also be a carboxylic acid ester, including MF, MA, EA, MP, etc. The additives include but are not limited to at least one of film-forming additives, conductive additives, flame retardant additives, anti-overcharge additives, additives for controlling the content of H2O and HF in the electrolyte, additives for improving low-temperature performance, and multifunctional additives.

[0041] Example 1

[0042] This embodiment 1 provides a composite aluminum-plastic film for a secondary battery, comprising a heat sealing layer 5, an aluminum foil layer 1, a thermally conductive adhesive layer 2 and a water-blocking and breathable layer 4, wherein the thermally conductive adhesive layer 2 comprises a thermally conductive adhesive and heat-absorbing particles 3 distributed in the thermally conductive adhesive.

[0043] Among them, the thermally conductive adhesive in the thermally conductive adhesive layer 2 is silicone grease, the heat-absorbing particles 3 are urea, the thickness of the thermally conductive adhesive layer 2 is 8μm, the urea particle size is 2μm, the urea doping amount is 40%, and the material of the water-blocking and breathable layer 4 is expanded polytetrafluoroethylene.

[0044] Preparation of the battery:

[0045] The positive electrode sheet, separator and negative electrode sheet are stacked and wound in sequence to form a battery cell. The prepared composite aluminum-plastic film is punched with holes to complete top and side sealing, liquid injection, formation, secondary sealing and folding with the battery cell to finally obtain a lithium-ion battery.

[0046] The preparation methods of Examples 2 to 7 and Comparative Examples 1 to 9 are the same as the preparation method of Example 1, except for the composition and parameters of the composite aluminum-plastic film, as shown in Table 1 below.

[0047] Table 1

[0048]

[0049]

[0050] The following performance tests were performed on the batteries prepared in the examples and comparative examples.

[0051] Hot box performance test: Place the battery in an oven, and raise the oven temperature at a rate of 5±2℃ / min to 130±2℃, 135±2℃, 140±2℃, 145±2℃ and maintain for 60 minutes before stopping. The battery surface temperature needs to be monitored during the test.

[0052] Judgment standard: The battery should not catch fire or explode within 60 minutes.

[0053] Among them, the above performance test results are shown in Table 2 below.

[0054] Table 2

[0055] Group 130℃ pass rate 135℃ pass rate 140℃ pass rate 145℃ pass rate Example 1 100% 100% 100% 100% Example 2 100% 100% 100% 40% Example 3 100% 100% 100% 50% Example 4 100% 100% 80% 20% Example 5 100% 100% 90% 30% Example 6 100% 100% 80% 30% Example 7 100% 100% 70% 20% Comparative Example 1 50% 10% 0% 0% Comparative Example 2 30% 10% 0% 0% Comparative Example 3 40% 20% 0% 0% Comparative Example 4 100% 80% 30% 0% Comparative Example 5 100% 80% 20% 0% Comparative Example 6 100% 60% 10% 0% Comparative Example 7 100% 50% 10% 0% Comparative Example 8 100% 50% 20% 0% Comparative Example 9 100% 50% 10% 0%

[0056] From the data comparison of Example 1 and Comparative Examples 1-3, it can be seen that when the composite aluminum-plastic film has a thermally conductive adhesive layer and a water-blocking and breathable layer, the prepared battery has excellent hot box performance. When it does not contain a thermally conductive adhesive layer and heat-absorbing particles, the heat absorption performance is poor, which further leads to poor hot box performance.

[0057] Among them, the comparison between Examples 1-3 and Comparative Examples 4-5 shows that the thickness of the thermally conductive adhesive layer has a certain influence on the performance of the hot box. When the thermally conductive adhesive layer is too thin, the heat dissipation improvement is small. When the thermally conductive adhesive layer is too thick, the heat is transferred to the aluminum layer slowly, which reduces the overall heat dissipation efficiency of the battery and has limited improvement on the performance of the hot box.

[0058] From the comparison between Examples 4-5 and Comparative Examples 6-7, it can be seen that the particle size of the heat-absorbing particles is an important factor affecting the thermal performance. If the particle size is too large, the heat-absorbing performance is poor, and if the particle size is too small, the particles will agglomerate and the performance improvement effect will be reduced.

[0059] From the comparison of Examples 6-7 and Comparative Examples 8-9, it can be seen that the doping of heat-absorbing particles has a significant impact on the performance of the hot box. If the doping amount is too small, the heat generated by the battery cannot be fully absorbed; if the doping amount is too large, there will be less silicone grease, reduced adhesion, reduced mechanical properties of the composite aluminum-plastic film, and reduced hot box performance.

[0060] According to the disclosure and teaching of the above description, those skilled in the art to which the present invention belongs can also change and modify the above embodiment. Therefore, the present invention is not limited to the above specific embodiment, and any obvious improvement, replacement or modification made by those skilled in the art on the basis of the present invention belongs to the protection scope of the present invention. In addition, although some specific terms are used in this specification, these terms are only for the convenience of description and do not constitute any limitation to the present invention.

Claims

1. A composite aluminum-plastic film for secondary batteries, characterized in that: From the inside to the outside, it includes an aluminum foil layer, a heat conductive adhesive layer, and a water-blocking and breathable layer; The surface of the water-blocking and breathable layer is distributed with a plurality of pores, the pore size of the pores is R1, the particle size of the water droplets is R2, and the particle size of the water vapor molecules is R3; wherein R1, R2, and R3 satisfy the relationship: R3<R1<R2; The thermally conductive adhesive layer includes a thermally conductive adhesive and heat absorbing particles distributed in the thermally conductive adhesive.

2. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The water-blocking and air-permeable layer is expanded polytetrafluoroethylene.

3. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The heat absorbing particles can be thermally decomposed to generate gas at a predetermined temperature, and the predetermined temperature for thermal decomposition is 100°C-150°C.

4. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The thickness of the thermal conductive adhesive layer is 5-10 μm.

5. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The particle size of the heat absorbing particles is 0.5-3 μm.

6. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The doping amount of the heat absorbing particles is 30-50%.

7. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The composite aluminum-plastic film further comprises a heat-sealing layer, and the heat-sealing layer is coated on the inner surface of the aluminum foil layer.

8. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The thermally conductive adhesive is silicone grease.

9. The composite aluminum-plastic film for secondary batteries according to claim 1, characterized in that: The heat absorbing particles are urea.

10. A secondary battery, characterized in that: The invention comprises the composite aluminum-plastic film for secondary batteries as claimed in any one of claims 1 to 9.